Faktor-Faktor Yang Memengaruhi Kinerja Sistem Informasi Akuntansi Dengan Pendidikan Dan Pelatihan Sebagai Variabel Moderasi Pada PT. Bukit Megagriya Makmur - Dyah Ayu Safitri; Muhammad Firdaus; Nurshadrina Kartika Sari (STIE Mandala Jember, 2021)
This study was conducted to determine the effect of user participation, user ability, and top management support on the performance of accounting information systems through education and training as moderating variables at PT. Megagriya Makmur Hill. This research uses classical assumption test, data quality test, descriptive statistical test, multiple linear regression, Moderated Regression Analysis test, and hypothesis testing. The results of the study show that user participation, user capabilities, top management support, have an effect on the performance of accounting information systems. When moderation occurs, education and training are not able to moderate user participation and top management support on accounting information system performance, while education and training are able to moderate users' ability to accounting information system performance.